THE AGARAK JAR BURIALS IN ARAGATSOTN:PRELIMINARY REPORT - Gabrielan, Armine Araratovna; Karapetan, Inesa Asotovna; Petrosan, Armenui (History, Archeology and Ethnography of the Caucasus, 2023)
The Classical-period burials at the site of Agarak are typologically diverse, including such forms as cist/stone chests, rock-cut tombs, simple ground burials, and jar burials. The last burial type appears frequently in the Hellenistic period of the region, and by the first centuries AD, it is widespread at settlements across Armenia (e.g. Artashat, Garni, Dvin, Vagharshapat, Avan, Shirakavan, Beniamin, Artsakh Tigranakert, etc.), and in the mortuary complexes of neighboring Georgia and Caucasian Albania. Between 2001 and 2012, excavations at the site of Agarak uncovered 10 jar burials, dating from the 6th century BC to 3rd century AD, most of which were deposited horizontally and in different directions. In order to inter the deceased, the vessel was broken at its shoulder or rim and the individual was placed inside in the fetal position. The vessel fragments were then repositioned in place. Through their grave goods, jar burials provide information about the everyday life, bodily adornments, and beliefs of the societies who buried their dead in this way. The study of the materials of the above-mentioned jar burials excavated in Agarak also indicated that these contained the same goods (ceramics, adornments, and coins) as other types of burials of the same burial field did. This fact testifies to the uniformity of material culture, differences in funeral rites while maintaining cultural unity and a similar worldview of the population of synchronized sites of Armenia.